Analisis Jaringan Instalasi Air Bersih di Summarecon Mall Bandung - Muhamad Ridho Adnan Yudhoyono; Olga Catherina Pattipawaej (Universitas Kristen Maranatha, 2025)
Planning and designing a clean water plumbing network system is an inseparable part of building construction. Soit must be carried out simultaneously and in accordance with the planning and design stages of the building, namely by paying attention to the relationship between the construction and distribution installations in meeting clean water needs evenly. This final project research was carried out at Summarecon Mall Bandung, with the aim of knowing and analyzing the need for clean water, the distribution system, and cost estimates presented in the form of a Bill of Quantity. Meanwhile, the scope of this Final Project includes analysis of distribution pipe networks in plumbing networks, discharge and flow velocity, as well as hydraulic analysis of clean water using EPANET 2.2 software. Based on the results of analysis using Epanet 2.2 software, it was obtained that the clean water discharge of the Summarecon Mall Bandung distribution network reached 15.50 liters/second, with an average of 6000 visitors/day and a minimum clean water requirement of 223 liters/person/day. The author's change in pipe diameter size resulted in a fluid pressure value flowing in the pipe (head loss) of 673.36 m/km or better than the initial design which had a head loss of 1051.30 m/km. Keywords: Epanet 2.2, Summarecon Mall Bandung, clean water reaching, average total loss of clean water